2019
DOI: 10.1101/804534
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Architecture of the chromatin remodeler RSC and insights into its nucleosome engagement

Abstract: Eukaryotic DNA is packaged into nucleosome arrays, which are repositioned by chromatin remodeling complexes to control DNA accessibility 1,2 . The Saccharomyces cerevisiae RSC (Remodeling the Structure of Chromatin) complex, a member of the SWI/SNF chromatin remodeler family, plays critical roles in genome maintenance, transcription, and DNA repair 2-4 . Here we report cryo-electron microscopy (cryo-EM) and crosslinking mass spectrometry (CLMS) studies of yeast RSC complex and show that RSC is composed of a ri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 53 publications
0
12
1
Order By: Relevance
“…5a, yellow circle). Several studies have recently reported that SWI/SNF remodelers engage the acidic patch on the opposite face of the nucleosome using their Sfh1 (RSC) or Snf5 (SWI/SNF) subunit (Fig 7e) [20][21][22]24,24 . This interaction is vital to the function of the enzyme, as mutations in a conserved basic domain in SMARCB1 (Snf5 homolog) disrupt binding to the nucleosome, reduce remodeling rates, and have defects in cell-type differentiation 40 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5a, yellow circle). Several studies have recently reported that SWI/SNF remodelers engage the acidic patch on the opposite face of the nucleosome using their Sfh1 (RSC) or Snf5 (SWI/SNF) subunit (Fig 7e) [20][21][22]24,24 . This interaction is vital to the function of the enzyme, as mutations in a conserved basic domain in SMARCB1 (Snf5 homolog) disrupt binding to the nucleosome, reduce remodeling rates, and have defects in cell-type differentiation 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Fig. 5) [20][21][22][23][24] . The C-terminal end of the HSA helix contacts the ATPase and engages with the post-HSA and P1 domains, as well as the Brace Helices ( Fig.…”
Section: Cryo-em Structure Of a Regulated Rsc Subcomplexmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the high-resolution structure of the RSC complex bound to a nucleosome has been solved by cryo-electron microscopy, revealing three flexibly connected parts [17][18][19]. The motor domain of the Sth1 subunit binds at superhelical location (SHL) +2, from where it translocates the DNA one base pair at a time into the direction of the dyad, possibly creating a loop that propagates around the nucleosome [20].…”
Section: Introductionmentioning
confidence: 99%
“…The ARP module, which couples DNA translocation and ATPase activity [21], connects the motor domain to the substrate recognition module (SRM). The latter contains DNA-binding Zn-cluster domains, five bromodomains, a histone-tail binding BAH domain and the nucleosome-binding C-terminal tail of Sfh1 [17][18][19]. Due to the flexible tethering of these domains, their structure, substrate preference, and interaction with the nucleosome remained largely unresolved.…”
Section: Introductionmentioning
confidence: 99%